Behaviour of User of Women Workers of Hero Supermarket Jakarta in Foster Family Pattern - Nurhablisyah Nurhablisyah (ADI Publisher, 2020)
Female workers have to face the reality in supporting family’s financial problem and taking care her children. This is not easy condition, they have to run their role as employee, mothers and wife. To run this decision,Female workers need support from family, parents and environment. The thing that can’t be avoided is, gadget usage as one of tools and gamess in family. The research methods use qualtitave with descriptive data analysis. The result was gained by distributing quesinare in Parenting Seminar which held by Hero Supermarket Workers Assocation in 16 th Mei 2016. The respondents were delegated Female Hero Supermarket workers from east Jakarta.The result showed From 39 responden, 92,3% or the respondent gave smartphone to their children. 35,9% respondent gave smartphone to their children to paly gamess, 20,5% to communicate with their children by whatsapp, message texting and telephone. The relationship and communication between respondents and their husband quite positive. 71,8% showed that they always discuss everything related to family’s matter to their husband, 51,3% don’t have any difficulties to communicate with their husband. Respondents understand that giving smartphone to toddlers will rise negative impact. That’s worry them, but they haven’t figure out the solution to this problem. Female workers in Hero Supermarket has limited access to parenting information. This encourage Hero Supermarket to held the seminar and balance the needs of the worker and make them feel comfort while working and raising their family.